Media Promotion of the Faculty of Computer Science, Bengkulu University, based on Multimedia - Wulandari Wulandari; Khairil Khairil; Siswanto Siswanto (Penerbit Jurnal Indonesia, 2021)
Multimedia is one of the existing information technology products. Multimedia has the power to attract interest in which multimedia combines various media sources such as text, images, sound, animation, and video and so on. Multimedia can be used in the fields of marketing, industry, commerce, entertainment, and education. Therefore, the writer will make an animated video as a promotion for the Faculty of Computer Science at the University of Dehasen Bengkulu using the Adobe After Effects CS6 application and assisted by the Adobe Illustrator CS6 and Adobe Photoshop CS6 applications. With the creation of promotional media for the Faculty of Computer Science, University of Dehasen Bengkulu in the form of animated videos, it is intended that it can help or be an alternative to promote the departments are in the Faculty of Computer Science, University of Dehasen Bengkulu to the public.